Best Proximity Points for Cyclic Contractions in CAT(0) Spaces - Nantadilok, Jamnian; Khunpanuk, Chainarong (Communications in Mathematics and Applications, 2021)
In this manuscript, we establish best proximity point results for some cyclic contraction maps. We discuss the existence and convergence of best proximity point results for such maps in CAT(0) spaces.